2012 International Symposium on Electronic System Design (ISED) 2012
DOI: 10.1109/ised.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Top and Bottom Contact Organic Transistor Performance for Different Technology Nodes

Abstract: This research paper analyzes the performance of organic thin film transistor (OTFT) for two typical structures, viz., bottom gate top contact (BGTC) and bottom gate bottom contact (BGBC). The analysis is carried out for channel length (L) from 5 to 50 μm. A significant reduction in drain current for top contact is observed, however, it remains constant for the bottom contact device. Transconductance of the top contact device falls about 50% from 5 to 10 μm L; however, for bottom contact only 1% reduction is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Fig. 3(a), (b) and (c) shows the output characteristics of organic thin-film transistor with uniform mobility and it is observed that the structural of the output characteristics is identical with the output characteristics of the conventional transistor [7]. Maximum drain current, I ds for channel length 50 µm is 1.066 µA as shown in Fig.…”
Section: Results Mobilitymentioning
confidence: 79%
“…Fig. 3(a), (b) and (c) shows the output characteristics of organic thin-film transistor with uniform mobility and it is observed that the structural of the output characteristics is identical with the output characteristics of the conventional transistor [7]. Maximum drain current, I ds for channel length 50 µm is 1.066 µA as shown in Fig.…”
Section: Results Mobilitymentioning
confidence: 79%